Physicochemical characteristics of fortified chicken nuggets with purple sweet potato flour (Ipomoea batatas L) - Purwanto, Andik Heni; dela Cruz, Joseph Flores; Harsita, Pradiptya Ayu; Purnamasari, Listya (Jurnal Teknologi Hasil Peternakan, 2026)
Chicken nuggets are a popular and practical processed meat product, but they are generally low in dietary fiber. Efforts to increase nutritional value can be done through fortification with functional food ingredients such as purple sweet potato flour (Ipomoea batatas L), which is known to be rich in fiber and bioactive compounds. This study aims to analyze the effect of the addition of purple sweet potato flour on the physicochemical characteristics of chicken nuggets. The study used a Complete Random Design (RAL) with four treatments, namely P0 (without purple sweet potato flour fortification), P1 (1% purple sweet potato flour fortification), P2 (2% purple sweet potato flour fortification), and P3 (3% purple sweet potato flour fortification) from the total dough, five replicates each. The parameters observed included pH, moisture content, cooking loss, and water holding capacity strength. The analysis data used ANOVA, and if the difference was significant (P<0.05) it was followed by Duncan's Multiple Range Test (DMRT). The results showed that the addition of purple sweet potato flour had no real effect on pH, moisture content, and water holding capacity (P>0.05), with a water holding capacity value of 60-61% and a pH of 5.69-5.78 which was still within the safe limit for consumption. However, fortification had a significant effect on cooking loss (P<0.05), with a value of 2.89-3.97%. The decrease in cooking loss shows the ability of purple sweet potato flour to increase water and fat retention during cooking so that it can improve the final quality of chicken nuggets.